Perilaku Keuangan sebagai Faktor Kunci Niat Kewirausahaan Islam pada Kalangan Santri di Sekolah Islam Modern - Indrawan Azhar; Poppy Laksita Rini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine how financial behavior based on Islamic principles influences Islamic entrepreneurial intentions among students at modern Islamic boarding schools in North Maluku. A quantitative method with an associative approach was used to analyze the relationship between the variables of Financial Literacy, Self-Control, and Saving Behavior on Islamic Entrepreneurial Intentions. Data were collected through questionnaires completed by 140 respondents and analyzed using Partial Least Squares Structural Equation Modeling. The findings show that financial literacy and self-control have a positive and significant direct influence on Islamic entrepreneurial intentions. In addition, saving behavior acts as a mediator that strengthens the relationship between financial literacy and self-control with entrepreneurial intention. These results emphasize the importance of implementing Islamic-based financial education and self-control training programs as a strategy to encourage ethical entrepreneurship among the younger generation, while strengthening the Islamic economic ecosystem through the development of comprehensive Islamic financial behavior.